Lifelong learning” is a new paradigm of personnel training in enterprises - Gogunskii, Viktor; Kolesnikov, Olexii; Kolesnikova, Kateryna; Lukianov, Dmytro (Eastern-European Journal of Enterprise Technologies, 2016)
World practice to overcome the lack of knowledge and meet educational needs under the terms of career growth and personal improvement and development is based on the modern paradigm of continuous postgraduate education ‑ lifelong learning (LLL). In the context of learning management, the analysis of features and synthesis of the structure of interaction of the basic process entities as knowledge holders were performed. Referring basic knowledge holders ‑ team, customer, training and in-depth knowledge systems to certain discrete states, which the system may take, allows representing the system using a Markov chain with four discrete states. A directed graph of the Markov chain reflects the secondary projection of a communication on the knowledge space rather than the physical interaction of the knowledge holders. Markov chain transition probabilities for the project environment define its characteristics that vary in discrete time by the steps in the form of a set of state probabilities. Cognitive properties of the model which is based on the Markov chain makes it possible to set some specific values of the transition probabilities of the system. The results obtained are the justification for continuing training and acquiring additional education of personnel in the deficit of knowledge that is necessary for the implementation of unique projects. Using the developed cognitive model of the interaction of knowledge in project management, the paradigm of “lifelong learning” was justified. The knowledge management structure includes four fundamental entities: the customer, the team, training and in-depth knowledge systems of the knowledge owners. These entities are in a constant process of knowledge sharing. The systems of training and in-depth knowledge play a role of generating new knowledge, which was absent in the project environment. Continuing education ideally is aimed at balancing between the needs of society and the motivational structure of personality that actually should be implemented through the mechanisms of the influence of education on the socialization of the individual.